Optimalisasi Pembekuan Sperma Limbah Kauda Epididimis Kambing Lokal dengan Metode Bertahap dan Stabilisasi - Naela Wanda Yusria Dalimunthe; M. Rosyid Ridlo; Agung Budiyanto (Jurnal Sain Veteriner, 2017)
Buck slaugthering produce waste such as testicles including epididymis which contain fertile sperm. Utilization of cauda epididymis as the sources of sperm for producing goat frozen sperm was not reported yet. The aims of this study were improving the frozen-thawed sperm using stabilization and multistep methods which recovered from the waste of buck slaughtering as the source of sperma. Cauda epididymis spermatozoa which was washed then diluted using extender 1 (Tris-citrate-antibiotics) and extender 2 (extender 1- glycerol-egg yolk). The extender 2 addition was performed by single or multistep methods then freezed. Modification in the pre freezing proces were performed by comparing the conventional equilibration and stabilization methods. The sperm suspension was incubated in 4°C for 2 hours after filling-sealing into straws on the equilibration group whether the stabilization group was cooled in tube 15 mL. All cooled straws from both groups were placed 4 cm horizontally on liquid nitrogen surface for 10 minutes and then plunged into liquid nitrogen for storage. The evaluation of motility parameters such as pattern of the movement and motility percentation were done followed the standard methodology. The student t-test, correlation and one-way ANOVA were used for data analysis with P<0.05. The results showed that multistep dilution method could increase the motility (25.0 ± 1.8 %) compared with single step (18.3 ± 1.7 %). Pre freezing method with stabilization also resulted higher motility (24.2 ± 2.0 %) than equilibration method (17.5 ± 2.8 %). The pattern of the movement were not different between all methods and its combination. The multistep dilution method and stabilization cooling method as well as its combination seems could increase the quality of frozen-thawed cauda epididymis spermatpzoa of local buck.